Identification of microRNA in Houttuynia cordata Thunb and prediction of cross kingdom functions - Jiajian He; Ting Chen; Qingyun Xi; Jiajie Sun; Junyi Luo; Meng Li; Haojie Zhang; Bin Zeng; Jiahan Wu; Yongliang Zhang (ExRNA)
Abstract Houttuynia cordata Thunb (Family: Saururaceae) is well known as a traditional medicine plant and widely spread in China, Japan and India. It had been reported to have potential functions such as anti-bacterial, anti-cancer, and anti-inflammatory in human. Recently, it has been reported that the plant-derived microRNA(miRNA) possibly transported from one species to another and exerted a cross kingdom regulation, and miRNA has been considered as medicinal ingredents in herbs. However, knowledge is still rare about miRNAs in H. cordata. In this study we identified 163 conserved miRNAs and 30 novel miRNAs by high-throughput sequencing, and then randomly selected miRNA’s expression trend was identified by q-PCR, which was consistent with the sequencing result. Further bioinformatics analyses showed that the targets of H. cordata miRNAs were enriched in endocrine and other factor-regulated calcium reabsorption pathways, melanogenesis, insulin signaling pathway, and aldosterone -regulated sodium reabsorption pathways. These results will be helpful to understand new active components in H. cordata as food and traditional Chinese medicine. This study is the first report of miRNAs in H. cordata, and provides valuable data for further understanding the cross kingdom function of active components in H.cordata.